ANALISIS MODAL SOSIAL DAN BIAYA TRANSAKSI UNTUK RELOKASI PEDAGANG KAKI LIMA, MUNGKINKAH? (STUDI KASUS DI JALAN JAWA-KABUPATEN JEMBER) - Suprianik Suprianik; Zainuri Zainuri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Activity street vendors nearby _ _campus University Jember who took place on the sidewalk and shoulder Street along Street Java . This thing because many buyer use part Street the place vehicle pass cross as the place parking for buyers _ street vendor _ that , as a result track for vehicle will reduce and. of course very disturbing Street so that cause congestion . Based on on background back above , then what becomes _ destination in writing this is for knowing how about social capital and cost transaction take effect to relocation street vendors in the Street Area Java districts Jember. by specific , result writing this state that social capital and cost transaction take effect in the process of relocation and transfer street vendor _ this proven no easy ask they for move from the place already there are those think already comfortable for they in trade. So that social capital is needed in the form of approach and strong trust for relocation trader this could done with good so that when the merchants will moved in place strategic new _ no occur existence clash in transfer that . Merchants _ also worrying about cost transaction to relocation in the form of cost a substitute for worried land _ rent increase expensive as well as the rules applied in _ the place new usually demand a number of Thing like setting appearance must - have cart interesting , standard cleanliness nor arrangement.